Mencetak SDM Unggul di UPTD BLKIP Disnakeresdm Provinsi Bali - Ida Bagus Ngurah Arda (Badan Riset dan Inovasi Daerah Provinsi Bali, 2019)
Good quality of human resources (HR) needs to be prepared in gacing the Industrial Revolution 4.0 in which one of the ways is by job training/vocational training. Vocational training needs to get important attention especially in Bali because it has flexibility in encouraging changes in community skills. The Provincial Government of Bali through the Unit Pelaksana Teknis Bidang Pelatihan yaitu UPTD Balai Latihan Kerja Industri dan Pariwisata, Dinas Tenaga Kerja dan Energi Sumber Daya Mineral Provinsi Bali, conduct skills training for the workforce in various vocational fields, both in the industrial and tourism fields, which has the aim of forming a workforce skilled, competent, and productive and in accordance with the needs of the workforce. There are three important stages that must be done in improving the quality of human resources through training and development activities. The first stage is identification of training needs, the second stage is training and development, the third stage is evaluation.